STUDY FOR A PASSIVE SCATTERING LINE DEDICATED TO RADIOBIOLOGY EXPERIMENTS AT THE TRENTO PROTON THERAPY CENTER. Issue 1 (11th December 2018) - Tommasino, F; Rovituso, M; Lorentini, S; La Tessa, C; Petringa, G; Cirrone, P; Romano, F; Scifoni, E; Schwarz, M; Durante, M
Abstract: The recent worldwide spread of Proton Therapy centers paves the way to new opportunities for basic and applied research related to the use of accelerated proton beams. Clinical centers make use of proton beam energies up to about 230 MeV. This represents an interesting energy range for a large spectrum of applications, including detector testing, radiation shielding and space research. Additionally, radiobiology research might benefit for a larger availability of proton beams, especially in those centers where a room dedicated to research activities also exists. Here, we describe the initial activities for the setup of a radiobiology irradiation facility at the Trento Proton Therapy Center. Data referring to the characterization of the beam in air are essential to that purpose and will be presented. A basic setup for large field irradiation will be also proposed, which is needed for the majority of in vitro and in vivo radiobiology experiments.